Sleep Disorders in US Military Personnel: A High Rate of Comorbid Insomnia and Obstructive Sleep Apnea - Mysliwiec, Vincent (Chest, 2013)
BACKGROUND: Sleep disturbances are among the most common symptoms of military personnel who return from deployment. The objective of our study was to determine the presence of sleep disorders in US military personnel referred for evaluation of sleep disturbances after deployment and examine associations between sleep disorders and service-related diagnoses of depression, mild traumatic brain injury, pain, and posttraumatic stress disorder (PTSD). METHODS: This was a cross-sectional study of military personnel with sleep disturbances who returned from combat within 18 months of deployment. Sleep disorders were assessed by clinical evaluation and polysomnogram with validated instruments to diagnose service-related illnesses. RESULTS: Of 110 military personnel included in our analysis, 97.3% were men (mean age, 33.6 ± 8.0 years; mean BMI, 30.0 ± 4.3 kg/m(2)), and 70.9% returned from combat within 12 months. Nearly one-half (47.3%) met diagnostic criteria for two or more service-related diagnoses. Sleep disorders were diagnosed in 88.2% of subjects; 11.8% had a normal sleep evaluation and served as control subjects. Overall, 62.7% met diagnostic criteria for obstructive sleep apnea (OSA) and 63.6% for insomnia. The exclusive diagnoses of insomnia and OSA were present in 25.5% and 24.5% of subjects, respectively; 38.2% had comorbid insomnia and OSA. Military personnel with comorbid insomnia and OSA were significantly more likely to meet criteria for depression (P < .01) and PTSD (P < .01) compared with control subjects and those with OSA only. CONCLUSIONS: Comorbid insomnia and OSA is a frequent diagnosis in military personnel referred for evaluation of sleep disturbances after deployment. This diagnosis, which is difficult to treat, may explain the refractory nature of many service-related diagnoses.